2021
DOI: 10.2147/ijgm.s323146
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Thromboembolism in Immune Thrombocytopenia: A Report of Five Cases and a Review of the Literature

Abstract: Objective To provide a reference for the diagnosis and treatment of patients with immune thrombocytopenia (ITP) complicated with pulmonary thromboembolism (PTE) by analyzing the clinical characteristics of five such patients. Methods This paper summarizes the clinical manifestations and hematological indexes of five patients with ITP complicated with pulmonary embolism. Results In this study, the incidence of ITP complicated with PTE was 2.75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…ITP patients have increased amounts of platelet and red cell microparticles [107]. Platelet microparticles are involved in thrombosis production through an increased procoagulant activity due to their higher content of large von Willebrand factor multimers that play an important role in platelet aggregation and coagulation [108]. Moreover, PMPs are potentially thrombogenic due to the high surface expression of phosphatidylserine [109].…”
Section: Thrombosis Related To Itp As a Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…ITP patients have increased amounts of platelet and red cell microparticles [107]. Platelet microparticles are involved in thrombosis production through an increased procoagulant activity due to their higher content of large von Willebrand factor multimers that play an important role in platelet aggregation and coagulation [108]. Moreover, PMPs are potentially thrombogenic due to the high surface expression of phosphatidylserine [109].…”
Section: Thrombosis Related To Itp As a Diseasementioning
confidence: 99%
“…Acquired deficiency of natural anticoagulants in ITP patients can be explained by complement activation, through the terminal complement complex that inhibits natural anticoagulant, which results in an increased risk of thrombosis [123]. Tan et al (2021) studied pulmonary thromboembolism in immune thrombocytopenia and showed that the level of antithrombin was deceased and the level of active protein C was increased, suggesting a link between these markers and thrombosis in this clinical context [108].…”
Section: Thrombosis Related To Itp As a Diseasementioning
confidence: 99%
“…ITP is characterized by the autoantibody-mediated destruction of platelets and the impaired production of platelets from megakaryocytes, [ 3 ] resulting in the decrease of platelet count (<100 × 10 9 /L), [ 4 ] with clinical manifestations of various bleeding tendencies, which is more likely to occur when platelets count <30 × 10 9 /L. [ 1 ] However, it has been reported that patients with this hemorrhagic disease have a risk of thrombosis and embolism in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The data of all 15 patients including our case are presented in ►Table 2. 1,[6][7][8][9][10][11][12][13] The underlying pathogenesis behind this prothrombotic tendency in patients with ITP is unclear. 14 Several different possible causes have been suggested including hyperactive immature platelets, 15 platelet microparticles, 14 and dysfunction in complement activation.…”
Section: Discussionmentioning
confidence: 99%